2000
DOI: 10.1111/j.1471-0528.2000.tb13229.x
|View full text |Cite
|
Sign up to set email alerts
|

A cost effectiveness analysis of goserelin compared with danazol as endometrial thinning agents

Abstract: Objective To analyse the cost, effectiveness and cost effectiveness of two endometrial thinning agents Setting A district general hospital.Design A retrospective cost effectiveness analysis, from the perspective of the health service, based ondata from an open, randomised, parallel group comparative study of 160 pre-menopausal women with dysfunctional uterine bleeding.Methods Within the trial, length of operation and duration of hospital stay was recorded for each woman. Resource use due to complications of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…A cost‐effectiveness analysis of preoperative endometrial suppression with danazol vs. GnRH agonists suggested the health care costs to be greater with GnRH agonists. However, the study also concluded that amenorrhea rates were slightly higher in the GnRH‐treated group, and the study withdrawals were greater in the danazol‐treated group (147).…”
Section: Methodsmentioning
confidence: 99%
“…A cost‐effectiveness analysis of preoperative endometrial suppression with danazol vs. GnRH agonists suggested the health care costs to be greater with GnRH agonists. However, the study also concluded that amenorrhea rates were slightly higher in the GnRH‐treated group, and the study withdrawals were greater in the danazol‐treated group (147).…”
Section: Methodsmentioning
confidence: 99%
“…Dysfunctional uterine bleeding (DUB), defined as excessive menstruation not due to recognizable pelvic or medical disease, has been traditionally treated with progestogens, oral contraceptive pills, danazol, and nonsteroidal anti‐inflammatory or antifibrinolytic agents. If hormonal therapy failed, hysterectomy was performed in 35–64% of the 70 000 hysterectomies in the UK (Sculpher et al ., 2000). But now a range of ‘minimal access’ procedures, such as endometrial ablation with destruction of the basal layer of the endometrium, may be performed.…”
mentioning
confidence: 99%
“…The items costed and source of unit costs (prices) are summarised in Table 1. [37][38][39][40][41] The calculation of the intervention costs is shown in Table 2. 3,42,43 Fixed costs, incurred through the expert input required for the content of the information pack and interview and the production of the booklet and video, are averaged over the total potential eligible population.…”
mentioning
confidence: 99%